Toxoplasma Gondii and Cognitive Deficits in Schizophrenia: An Animal Model Perspective - Kannan, Geetha (Oxford University Press, 2012)
Cognitive deficits are a core feature of schizophrenia. Epidemiological evidence indicates that microbial pathogens may contribute to cognitive impairment in patients with schizophrenia. Exposure to Toxoplasma gondii (T. gondii) has been associated with cognitive deficits in humans. However, the mechanisms whereby the parasite impacts cognition remain poorly understood. Animal models of T. gondii infection may aid in elucidating the underpinnings of cognitive dysfunction. Here, we (1) overview the literature on the association of T. gondii infection and cognitive impairment, (2) critically analyze current rodent models of cognitive deficits resulting from T. gondii infection, and (3) explore possible mechanisms whereby the parasite may affect cognitive function.